(untitled) - Davidsen, Susanna (Chicago, 2004)
This book is a gift all libraries who sense, deep down, that their libraries web site needs a serious makeeover but want to do it correctly from the ground up. In the firm but comfortable grip of authors Sue Davidsen and Everul Yankee, you will learn that a web site exists first and foremost for its users-not to satisfy a designer's whim or to appease the maintainers' need for ease of use.
Keywords: Trang web thư viện,Library web sites,Websites; Thiết kế web,Design